DETERMINANT ANALYSIS OF PROFITABILITY OF CONVENTIONAL COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE - Serly Serly; Meily Juliani; Androni Susanto; Rudi Candra; Nolivia Nolivia (Institute of Computer Science (IOCS), 2022)
This study aims to determine the factors that determine the profitability of conventional commercial banks listed on the Indonesia Stock Exchange in the 2016-2020 period. Profitability in this study was measured using 2 (two) proxies, namely Return on Assets (ROA) and Return on Equity (ROE). The method used in this study uses quantitative methods with data obtained from financial statements issued by each bank, or the official website of the Indonesia Stock Exchange and the Financial Services Authority. The population in this study were all conventional commercial banks listed on the Indonesia Stock Exchange. This study uses a purposive sampling technique with predetermined criteria. There are 40 conventional commercial banks that are included in the sample criteria. The results of this study indicate that there is a significant effect of loan to asset, operating expenses on operating income (BOPO), labor costs to income, non-performing loans. (NPL), Capital Adequacy Ratio (CAR), while bank size, security specialization, and deposit specialization have no significant effect on ROA. Variables Bank size, BOPO, labor cost to income have a significant effect on ROE, while loan to assets, security specialization, deposit specialization, NPL, and CAR have no significant effect on ROE